Pretreatments Effect in Drying Behaviour and Colour of Mature and Immature ‘Napolitana’ Sweet Cherries - Pirone, Beatriz N. (2014)
The effect of different treatments on drying behaviour and colour of mature and immature cherries (Napolitana var.) has been studied. Drying was carried out at 70 °C with air at 4 m/s speed and 8 % relative humidity, and fruits were subjected to the following pretreatments: B (blanching), F (freezing), P (pitting), B + Dip1 (blanching and immersion in acid solution) and B + Dip1 + Dip2 (blanching and immersion in saline acid solution) which affected the drying behaviour and the colour retention of fruits for both maturity degrees. Regarding skin colour in terms of chroma and hunter a parameters, the anthocyanin retention and the evaluation of anthocyanin degradation index, both B + dip1 and B + dip1 + dip2 pretreatments led to better-quality dry products, mainly in mature cherries. Moreover, the incorporation of blanching in the combined pretreatments significantly reduced drying time. Lewis, Page and Logarithmic models were selected to represent in a simple way the thin-layer drying characteristics of pretreated cherries and to predict the process times required to reduce the moisture content to about 0.3-0.4 kg water/kg dm (aw ≤ 0.6). Logarithmic model provided the best fit to experimental data for each drying curve, based on the statistical tests used for evaluation.